'Walton', a new virginia‐type peanut suitable for Virginia and northern U.S. growing regions. Issue 3 (28th June 2021) - Balota, Maria; Tillman, Barry L.; Paula‐Moraes, Silvana V.; Anco, Dan
Abstract: 'Walton' (Reg. no. CV‐146, PI 695073) is a virginia‐type peanut ( Arachis hypogaea L. subsp. hypogaea var. hypogaea ) with desirable agronomic characteristics and yield stability in the northernmost peanut growing region of the United States, the Virginia–Carolina (VC) region. Walton was tested under the experimental designation 08x09‐3‐14‐1 and was released in 2019 jointly by the University of Florida and Virginia Tech. Walton was initially evaluated in Marianna, FL, during 2014 and subsequently in Virginia, North Carolina, Florida, and South Carolina during 2015–2018. In these tests, Walton was similar for yield, grade, and economic value to 'Bailey', 'Bailey II', and 'Emery' and outperformed 'Sullivan' and 'Wynne'. Oleic fatty acid (C18:1) content was significantly higher than for Bailey II and Wynne. In Virginia, Walton produced greater yields regardless of digging time than Bailey, Sullivan, and Wynne. Under rainout shelters, Walton yielded highest under both water regimes—deficit and full irrigation. Under water deficit, Walton yielded similarly to GP‐NC WS17, a drought‐tolerant, species‐derived germplasm line, and significantly greater than the cultivars Bailey, 'Florida‐07', Sullivan, and Wynne. Thus, the release of Walton provides VC peanut producers with a profitable, high‐oleic option robust to weather fluctuations and digging dates. Core Ideas: 'Walton' is a high‐yielding peanut cultivar adapted to the northmost U.S. peanut growing region. Under water deficit, Walton yielded greater than the current virginia‐type cultivars. Walton is high‐oleic, early maturing, and resistant to the soybean looper.